GAMBARAN TINGKAT PENGETAHUAN PUSTAKAWAN PERGURUAN TINGGI MUHAMMADIYAH ‘AISYIYAH/ PTMA TENTANG KONSEP LIBRARY 4.0 - Irkhamiyati Irkhamiyati (Ikatan Pustakawan Indonesia, 2019)
The purpose of this study was to determine the description of the level of knowledge of PTMA Librarians about the concept of Library 4.0. The benefits of this research are in addition to the knowledge of PTMA librarians in particular, and other librarians in general. This research is quantitative descriptive, using a cross sectional design. The variable is the knowledge level of the PTMA Librarian about the concept of the Library 4.0 concept. Time of study in April-May 2019. Place of research in the PTMA Library. The technique of collecting data through a questionnaire in Google Form. Random sampling was 43 people (25% WAG FPPTMA members). The validity test using the Exel program with the Biserial Point Correlation formula (Correl function). Reliability test using the formula Kuder Richardson 21 / KR21 through Exel. Processing data through the editing and scoring stages. The results of the validity test show 12 invalid questions which will then not be used in the research questionnaire. The reliability test results are 0.81 which indicates T Count greater than 0.70, so that the instrument is declared reliable. The results of the study showed that most of the levels in good knowledge were 22 people (51%). The midle level of knowledge is 10 people (23%), and there is less knowledge of 11 people (26%). Characteristics of the respondents were mostly undergraduate education with as many as 25 respondents (58%), most of them were library staff, 26 people (60%), most of them were adults (20-34 years) which were 26 respondents (60%), some large sources of information about the concept of Library 4.0 through seminars and the like, namely 36 people (84%), and most of the majority of women were 26 people (60%). PTMA librarians must to increase their level of knowledge about the Library 4.0 concept is still lacking, in order to increase their knowledge through various sources and through other activities. For PTMA libraries and other libraries to begin to understand the concept of Library 4.0 which can then begin to be applied in accordance with their respective abilities.